1977
DOI: 10.1128/jb.131.3.741-744.1977
|View full text |Cite
|
Sign up to set email alerts
|

Zeatin ribonucleosides in the transfer ribonucleic acid of Rhizobium leguminosarum, Agrobacterium tumefaciens, Corynebacterium fascians, and Erwinia amylovora

Abstract: Until recently, the presence in transfer ribonucleic acid (tRNA) ofthe hydroxylated cytokinin ribosylzeatin [N6-(4-hydroxy-3-methylbut-2-enyl)adenosine] was thought to be unique to higher plants. This extension of work from several laboratories indicates the presence of 2-methylthioribosylzeatin in the tRNA of the plant-associated bacteria Rhizobium leguminosarum, Agrobacterium tumefaciens, and Corynebacterium fascians, but not in that of Erwinia amylovora. This cytokinin has the cis configuration, as is norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The experiments presented here clearly establish the presence of trans-ms2iO6A in the tRNA of A. vinelandii. The tRNAs of bacteria such as R. leguminosarum, A. tumefaciens, and Pseudomonas aeruginosa have been reported to contain the cis isomer of ms2iO6A (13,14,33). Thus, the presence of the trans isomer in A. vinelandii tRNA is a new finding.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The experiments presented here clearly establish the presence of trans-ms2iO6A in the tRNA of A. vinelandii. The tRNAs of bacteria such as R. leguminosarum, A. tumefaciens, and Pseudomonas aeruginosa have been reported to contain the cis isomer of ms2iO6A (13,14,33). Thus, the presence of the trans isomer in A. vinelandii tRNA is a new finding.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it has been suggested that only plants have the gene for the hydroxylating enzyme which converts i6A and ms2i6A to the respective hydroxylated derivatives iO6A and ms2iO6A (32). Bacteria such as Rhizobium leguminosarum, Agrobacterium tumefaciens, and Corynebacterium fascians have been shown to contain iO6A or ms2iO6A in their tRNA (12)(13)(14)23). This indicated the presence of hydroxylase, implying that these bacteria acquired the gene for the hydroxylase activity from the plants during their association over long periods of time (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…666 Physiol, Plant, 101, 1997 Once the adenosine residue has been isopentenylated, it may be further modified by side chain hydroxylation and/or ring methylation to give cytokinin derivatives such as c/5-ribosylzeatin or 2-methylthioribosylzeatin (Cherayil and Lipsett 1977).…”
Section: Biosynthesis Of Cytokinins Via Trnamentioning
confidence: 99%
“…While T-DNA phytohormone genes are expressed in crown gall tumors, other phytohormone-related loci are expressed in A. tumefaciens. The bacterium produces both auxins (23)(24)(25)(26) and cytokinins (27)(28)(29)(30)(31)(32)(33)(34). The production of auxins by strain C58 has been reported to involve two genetic loci, one chromosomal (iaaC) and one plasmid-borne (iaaP) (26).…”
Section: Introductionmentioning
confidence: 99%